2016
DOI: 10.1177/1557988315569593
|View full text |Cite
|
Sign up to set email alerts
|

“I Want a Second Chance”

Abstract: With over 700,000 people on average released from prison each year to communities, greater attention is warranted on the experiences and needs of those who are parents and seeking to develop healthy relationships with their children and families. This study seeks to explore the experiences of African American fathers in reentry. Qualitative data from 16 African American men enrolled in a fellowship program for fathers were collected from a focus group and analyzed for common themes and using standpoint theory.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 47 publications
(49 reference statements)
0
3
0
Order By: Relevance
“…Marked with stigma and pervasive marginality, returning citizens are substantially less likely to secure employment than nonincarcerated individuals (Silver et al, 2021), they report more stress associated with strained family relationships (Liu & Visher, 2019; Liu et al, 2021), and the majority do not have access to needed medical or psychiatric care (Mallik‐Kane & Visher, 2008; Salem et al, 2021; Williams et al, 2020). In their qualitative study of Black fathers, Dill et al (2016) identified several barriers impeding community transition and healthy family relationships, including difficulty accessing affordable housing and obtaining financial stability. These findings highlight the diverse unmet needs of Black returning citizens and the hurdles they face during reintegration into under‐resourced, low‐income communities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Marked with stigma and pervasive marginality, returning citizens are substantially less likely to secure employment than nonincarcerated individuals (Silver et al, 2021), they report more stress associated with strained family relationships (Liu & Visher, 2019; Liu et al, 2021), and the majority do not have access to needed medical or psychiatric care (Mallik‐Kane & Visher, 2008; Salem et al, 2021; Williams et al, 2020). In their qualitative study of Black fathers, Dill et al (2016) identified several barriers impeding community transition and healthy family relationships, including difficulty accessing affordable housing and obtaining financial stability. These findings highlight the diverse unmet needs of Black returning citizens and the hurdles they face during reintegration into under‐resourced, low‐income communities.…”
Section: Introductionmentioning
confidence: 99%
“…Hlavka et al (2015) assert that offenders who can manage the stigma of “spoiled identities” are better placed to obtain successful re‐entry. Positive beliefs about one's future self related to success and accomplishment, such as the need for redemption or a “second chance” are also integral in overcoming re‐entry barriers (Dill et al, 2016; Giordano et al, 2002; Gurusami, 2017). Such studies highlight the complex nature of the re‐entry process and provide evidence that varied perceptions of re‐entry influence the behavior of returning citizens.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, father involvement with children is often a competing priority for men, leading to steps that promote successful parent–child engagement (Charles et al, 2021). Fathers not only seek out housing and employment to support reunification goals with their children but often attribute children as a primary motivator for desistance to crime (Charles et al, 2019; Dill et al, 2016).…”
Section: Introductionmentioning
confidence: 99%